2019
DOI: 10.1101/600890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cas12a trans-cleavage can be modulated in vitro and is active on ssDNA, dsDNA, and RNA

Abstract: CRISPR-Cas12a (Cpf1) are RNA-guided nuclease effectors of acquired immune response that act in their native organisms by cleaving targeted DNA sequences. Like CRISPR-Cas9 RNA-guided DNA targeting enzymes, Cas12a orthologs have been repurposed for genome editing in non-native organisms and for DNA manipulation in vitro. Recent studies have shown that activation of Cas12a via guide RNA-target DNA pairing causes multiple turnover, non-specific ssDNA degradation in trans, after single turnover ontarget cleavage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 55 publications
(76 reference statements)
13
48
0
Order By: Relevance
“…To measure the collateral or trans-cleavage activity of Cas12a, we employed a FRET-based reporter used in DETECTR 1 , composed of a fluorophore (FAM) and a quencher (3IABkFQ) connected by a 5nucleotide sequence (TTATT), which displays increased fluorescence upon cleavage. Consistent with the previous literature 13 , when using wild-type crRNAs, we observed that the LbCas12a exhibited higher trans-cleavage activity than the AsCas12a or the FnCas12a, and therefore, we designed various modified crRNAs compatible with LbCas12a. Using the same reporters, we discovered that ssDNA and ssRNA extensions on the 3′-end of crGFP markedly enhanced the trans-cleavage ability of targetactivated LbCas12a.…”
Section: Resultssupporting
confidence: 85%
“…To measure the collateral or trans-cleavage activity of Cas12a, we employed a FRET-based reporter used in DETECTR 1 , composed of a fluorophore (FAM) and a quencher (3IABkFQ) connected by a 5nucleotide sequence (TTATT), which displays increased fluorescence upon cleavage. Consistent with the previous literature 13 , when using wild-type crRNAs, we observed that the LbCas12a exhibited higher trans-cleavage activity than the AsCas12a or the FnCas12a, and therefore, we designed various modified crRNAs compatible with LbCas12a. Using the same reporters, we discovered that ssDNA and ssRNA extensions on the 3′-end of crGFP markedly enhanced the trans-cleavage ability of targetactivated LbCas12a.…”
Section: Resultssupporting
confidence: 85%
“…In order to measure the collateral or trans-cleavage activity of Cas12a, we employed a FRET-based reporter used in DETECTR, 1 composed of a fluorophore (FAM) and a quencher (3IABkFQ) connected by a 5-nucleotide sequence (TTATT), which displays increased fluorescence upon cleavage. Consistent with the previous literature 13 , respectively. The fold in fluorescence was normalized by taking the ratio of background-corrected fluorescence signals of sample with activator to the corresponding sample without activator.…”
supporting
confidence: 92%
“…Overall, LbCas12a showed the highest fluorescence signal, which is consistent with previous studies. 13,18 Through observation of the fluorophore-quencher-based reporter assay and time-dependent gel electrophoresis, we hypothesized that the various extensions of ssDNA on the crRNA induce conformational changes on LbCas12a that result in enhanced endonuclease activity.…”
mentioning
confidence: 99%
“…We also establish that Cas12a has non-specific dsDNA nicking activity upon binding to a crRNA-complementary DNA. While this manuscript was in preparation, a complementary study reported similar observations, demonstrating that these activities are reproducible in vitro (42).…”
Section: Discussionsupporting
confidence: 59%
“…This may be attributed to decreased breathing and exposure of ssDNA sites. It remains unclear how negatively supercoiled plasmids are nicked multiple times leading to linearization; however, multiple events of the trans nicking activity may cause the DNA to eventually fall apart (42). This suggests that a cumulative effect of all the trans activities of Cas12a eventually leads to complete degradation of nucleic acid substrates (Fig.…”
Section: Discussionmentioning
confidence: 99%